The association of the lipidomic profile with features of polycystic ovary syndrome - Moran, L J; Mundra, P A; Teede, H J; Meikle, P J (Journal of molecular endocrinology, 2017)
Polycystic ovary syndrome (PCOS) affects up to 18% of reproductive-aged women with reproductive and metabolic complications. While lipidomics can identify associations between lipid species and metabolic diseases, no research has examined the association of lipid species with the pathophysiological features of PCOS. The aim of this study was to examine the lipidomic profile in women with and without PCOS. This study was a cross-sectional study in 156 age-matched pre-menopausal women (18-45 years, BMI >20 kg/m ; = 92 with PCOS, = 64 without PCOS). Outcomes included the association between the plasma lipidomic profile (325 lipid species (24 classes) using liquid chromatography mass spectrometry) and PCOS, adiposity, homeostasis assessment of insulin resistance (HOMA), sex hormone-binding globulin (SHBG) and free androgen index (FAI). There were no associations of the lipidomic profile with PCOS or testosterone. HOMA was positively associated with 2 classes (dihydroceramide and triacylglycerol), SHBG was inversely associated with 2 classes (diacylglycerol and triacylglycerol), FAI was positively associated with 8 classes (ceramide, phosphatidylcholine, lysophosphatidylcholine, phosphatidylethanolamine, lysophosphatidylethanolamine, phosphatidylinositol, diacylglycerol and triacylglycerol) and waist circumference was associated with 8 classes (4 positively (dihydroceramide, phosphatidylglycerol, diacylglycerol and triacylglycerol) and 4 inversely (trihexosylceramide, G ganglioside, alkenylphosphatidylcholine and alkylphosphatidylethanolamine)). The lipidomic profile was primarily related to central adiposity and FAI in women with or without PCOS. This supports prior findings that adiposity is a key driver of dyslipidaemia in PCOS and highlights the need for weight management through lifestyle interventions.